Whole-brain Radiation Therapy for Intracranial Metastases as Initial or Late Treatment - HIRANUMA, HISATO (In Vivo, 2021)
Background/Aim: We examined the difference between whole-brain radiation therapy (WBRT) for intracranial metastases (IM) from lung cancer as an initial and as a late treatment affecting overall survival (OS). Patients and Methods: Thirty-three patients who presented with IM at initial examination who received WBRT as the initial treatment (initial WBRT group) and 47 patients without IM or with asymptomatic IM at initial examination who received WBRT after systemic therapy, between January 2014 and December 2020, were retrospectively analyzed. Patients’ OS after WBRT were compared. Results: Median OS was significantly longer in patients treated with systemic anticancer therapy after WBRT than in patients who were not (176 vs. 47 days, respectively; p<0.001), and systemic anticancer therapy after WBRT was a significant prognostic factor (p<0.001). Conclusion: Treatment with systemic anticancer therapy after WBRT may prolong the survival of patients who present with IM at initial examination.